2019
DOI: 10.1115/1.4042825
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Auto-Ignition Characteristics in Microstructured Catalytic Honeycomb Reactor for CH4–Air and CH4–H2–Air Mixtures

Abstract: Stable ranges of auto-ignition for the microcombustion of CH4 and CH4–H2 mixtures are identified numerically in a platinum-coated microcatalytic honeycomb reactor. Steady and transient simulations under pseudo-auto-thermal conditions were performed to investigate the coupling phenomenon between combustion and heat transfer in such microburner using ANSYS 17.2 coupled with a detailed chemkin reaction mechanism. The model was validated utilizing the available data in the literature on a similar microreactor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Studies have shown preheating and heat recirculation can improve fuel conversion [9,28]. Combined with the early efforts to simulate the catalytic combustion [12,27,31,32], a better model of the chemistry and device performance can be developed. For now, the empirical results provide a strong motivation for developing a robust chemical model for such a system that is predictive of device performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown preheating and heat recirculation can improve fuel conversion [9,28]. Combined with the early efforts to simulate the catalytic combustion [12,27,31,32], a better model of the chemistry and device performance can be developed. For now, the empirical results provide a strong motivation for developing a robust chemical model for such a system that is predictive of device performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analytical, experimental, and numerical studies focused primarily on the stable and weak flame modes for various fuel mixtures and under various operating conditions. These studies provided insight to understand the concepts of low-temperature ignition (LTI), cool flames, and the influence of the negative temperature coefficient (NTC) region [4,12,[16][17][18][19][20][21]. It has been shown that cool flames are usually generated in the unburned fuel mixture region, while another conventional flame propagates through the reacting mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this work is to scrutinize the combustion characteristics and flame behavior for various inlet velocities (0.1-0.6 m/s), equivalence ratios representing the fuel-lean (φ = 0.6, 0.8), stoichiometric (φ = 1), and fuel-rich (φ = 1.2, 1.4) conditions, and channel diameters of 1.8 mm, 2.3 mm, and 3 mm, resulting in simulating a total of 34 unique cases with 2 to 5 days needed to complete each simulation using highperformance computers, depending on the operating conditions and the flame behavior. Varying these parameters, the flame can become stable or experience repeated extinctions and ignitions [11,21,29,30]. It is important to highlight that the models and the methods employed in this work have been accepted and acknowledged in the literature [24,27].…”
Section: Introductionmentioning
confidence: 99%